Analisis Penggunaan Bahasa di Sosial Media terhadap Kesehatan Mental Remaja - A Nurhayati; Husnani Aliah; Sarmila Sarmila (FKIP, Universitas Palangka Raya, 2026)
Social media has become an integral part of the life of modern adolescents. They spend a lot of time communicating, interacting, and sharing content on social media platforms. The study aims to provide a deeper understanding of the kinds of languages used by adolescents on social media, including the use of positive, negative, or ambiguous words. The results of this study are expected to contribute to our understanding of the impact of language use on social media on adolescent mental health. The design of the research used is a case study, This research is a qualitative research, Qualitative approaches are used to gather data, take meaning, and gain an understanding of the impact of language use in social media as well as the relationship of its impact on adolescent mental health, Location of research carried out In the South Sulawesi Province, the city of Palopo, In addition, the data also includes interviews and documentation with several individuals who are actively using social media to reflect their experiences and approaches to the influence of language on social media. A large number of respondents felt that unpleasant content, disrespectful comments, and comparing themselves to others on social media could have a negative impact on their mental health.